Proton affinities of organic molecules by the kinetic method and a mass spectrometric study of immonium ions by tandem mass spectrometry. - Cao, Jie. (University of Ottawa (Canada), 2001)
The systematic study of the kinetic method has been carried out by observing a wide variety of proton-bound pairs consisting of amines, nitriles and alkanols using tandem mass spectrometry. The majority of the compounds studied were homologous alkyl series. The results were obtained for other selected amines such as pyridine, allylamine, benzylamine and phenylethylamine. The proton affinities of many of these compounds are well established in the NIST database, although some needed either to be revised or to be given their first experimental values. For the competitive dissociations of proton-bound dimers, which were studied under MI and CID conditions, the relative product yields, [B 1H+]/[B2H+], have been related to the proton affinities (PA) of B1 and B2 by the kinetic method. In its simplest form, the method assumes that there are no entropy effects and a zero reverse energy barrier for the competing dissociations. The general effects expected from non-zero entropies of activation are described in terms of how they influence log k(rate constant) vs. E(internal energy) plots for such competing dissociations. For these homologous series such effects were observed to be minimal and the kinetic method well reproduces most of the reference PA values. However, in view of the very close agreement between the present results and many reference PA values obtained from equilibrium studies, it is possible that small reverse energy barriers (ca. 5 kJ mol -1) may in some cases be identifiable by the kinetic method, in particular for t-C4H9NH2, the homologous di-n-alkylamines and possibly larger barriers for di-sec-alkylamines. The method is quite sensitive to small discrepancies in PA and new values have been proposed for C6H5CH2NH2 (923 kJ mol-1), C6H5CH2CH 2NH2 (930 kJ mol-1), (CH3)(n-C 4H9)NH (951 kJ mol-1), (i-C4H 9)2NH (969 kJ mol-1) and for homologous nitriles and alkanols, namely from C5 to C8. The PA value for n-C4H9OH was revised from 789.2 to 793.7 kJ mol-1. Second part of the thesis regards the following aspects: (A) Investigation of the a-cleavage mechanism in simple amine molecular ions and (B) Mass spectrometric studies of immonium ions, CH3CH2CH +NH2 and (CH3)2C+NH 2 and their oxygen analogues. (Abstract shortened by UMI.)
Keywords: Chemistry, Analytical.